D-dimer and NLR Levels as Potential Biomarkers to Predict Mortality in Patients with Covid-19 - Andi Priscillia Al-qodri; Meta Hawika Putri (Sriwijaya Journal of Medicine, 2022)
Introduction: Due to the high mortality of the coronavirus disease 2019 (Covid-19) pandemic that continues to strain healthcare systems, early and effective predictors of clinical outcomes are urgently needed to improve management of Covid-19 patients. The aim of this study was to evaluate whether elevated levels of D-dimer and NLR combination could predict mortality in patients with Covid-19. Methods: A total of 60 eligible patients with laboratory confirmed Covid-19 were retrospectively enrolled in Intensive Care Unit of Raden Mattaher Hospital from November 2020 to April 2021. D-dimer value on admission and death events were collected to calculate the optimum cutoff. Results and discussions: The optimum cut off values of D-dimer; NLR to predict in-hospital mortality were ≥2.1 μg/ml; ≥8.09% with both sensitivity 70.4% and specificity 72.7% (P = 0.001). There were 17 patients with D-dimer; NLR value ≥2.1 μg/ml; ≥8.09% on admission, and 15 deaths (88.2%) occurred during hospitalization. Conclusions: D-dimer; NLR values on admission ≥2.1 μg/ml; ≥8.09% could predict in-hospital mortality in patients with Covid-19, which indicated D-dimer and NLR could be an early and helpful markers to improve management of Covid-19 patients.